Ne plus se laisser prendre à leurs Jeux. - Anaïs Bohuon; Lucie Pallesi (Cahiers d’histoire.)
Today recognized with embarrassment by sports institutions, intersex and trans-identity would fundamentally call into question a basic principle of competition according to which the gender bicameralization would guarantee equity, especially for the women category. From both a scientific and a sociocultural point of view, the management of gender identity by sports authorities is very insufficient. The recent and publicized cases of trans or intersex women excluded from competitions shake up the hitherto inflexible logic of sexual duality and renew the controversy. Because they are the first victims of the mechanisms for maintaining the system of gender bicategorization in sport, some intersex and trans athletes create a counter-discourse to the hegemonic one of equity. In the 1970s and 1980s, the exclusion of certain athletes led them to use the reasoning of institutions on the supposed «natural» physical inferiority of women to be rehabilitated. In the 2010s, a more assertive form of activism emerged with the mobilization of legal tools from athletes challenging the rules of federations restricting their participation, in particular the maximum testosterone levels imposed in the women’s category.